Design of Molecular Spintronics Devices Containing Molybdenum Oxide as Hole Injection Layer. (6th January 2017) - Prieto‐Ruiz, Juan Pablo; Miralles, Sara G.; Großmann, Nicolas; Aeschlimann, Martin; Cinchetti, Mirko; Prima‐García, Helena; Coronado, Eugenio
Abstract : Molybdenum oxide (MoOx ) is a very promising material, as it creates an interfacial dipole that increases the metal work function of the electrode. In organic electronic devices, this causes an improvement of the injection of carriers from the metal electrode into the HOMO of the organic semiconductor. However, up to now, MoOx has never been employed in molecular spintronics.